2020
DOI: 10.7124/feeo.v26.1282
|View full text |Cite
|
Sign up to set email alerts
|

Alanine scanning of dinitroaniline/phosphorothioamidate site of α-tubulin in plasmodium species distributed in India

Abstract: Aim. Identification of amino acid residues participating in specific binding of dinitroaniline and phosphorothioamidate compounds with α-tubulin in Plasmodium falciparum. Methods. Protein structure modelling, protein structure optimization using molecular dynamics method, ligand-protein docking, alanine scanning mutagenesis. Results. Molecular docking of canonical compounds and alanine scanning mutagenesis, indicate two key (Arg2, Val250) and one minor (Glu3) residues involved in binding of both - dinitroanili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…From the interactive site analysis, it was evident that the α1-, α2-, β-, and γ-tubulins of P. falciparum were sharing a common binding pocket with amino acid residues Gln11, Ala12, Ile14, Gln91, Leu92, Ala100, Thr143, Gly144, Tyr179, Ala180, and Arg228 with the presence of GTP and GDP (Figures S8−S10). A recent study has shown that residues Arg2, Gln133, Arg243, Asn249, Val250, Asp251, Val252, Thr253, and Glu254 are parasite α-tubulin-specific, 17 and a detailed comparative analysis of the four tubulin proteins with human tubulins revealed that Leu92 and Arg228 are found to be parasite-specific, which were lying around the same active region. Additionally, we found that the amino acid residues Ala12, Ile14, Gln91, Ala100, Tyr179, and Ala180 present in α1-, α2-, and β-tubulins are parasite-specific too.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the interactive site analysis, it was evident that the α1-, α2-, β-, and γ-tubulins of P. falciparum were sharing a common binding pocket with amino acid residues Gln11, Ala12, Ile14, Gln91, Leu92, Ala100, Thr143, Gly144, Tyr179, Ala180, and Arg228 with the presence of GTP and GDP (Figures S8−S10). A recent study has shown that residues Arg2, Gln133, Arg243, Asn249, Val250, Asp251, Val252, Thr253, and Glu254 are parasite α-tubulin-specific, 17 and a detailed comparative analysis of the four tubulin proteins with human tubulins revealed that Leu92 and Arg228 are found to be parasite-specific, which were lying around the same active region. Additionally, we found that the amino acid residues Ala12, Ile14, Gln91, Ala100, Tyr179, and Ala180 present in α1-, α2-, and β-tubulins are parasite-specific too.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A recent study has identified a parasite-specific binding site in Plasmodium α-tubulin, similar to plant α-tubulin but absent in human α-tubulin. , Recent advancements in structural bioinformatics, especially the methods based on comparative modeling, active site analysis, and protein simulations, have significantly progressed, which even facilitate the discovery of sites specific to a group of proteins . A potential target must be essential for the pathogen, and further designing of inhibitors should hinder the function exclusively to pathogen and should avoid the undesirable cross-reactivity with the human proteins.…”
Section: Introductionmentioning
confidence: 99%